2020
DOI: 10.1002/cae.22306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an online augmented reality puzzle for DC circuits: Students' feedback and conceptual knowledge gain

Abstract: Augmented reality (AR) enables users to overlay new information over the real environment, allowing them to get a clear perception of physical systems or even to interact with them. AR is a powerful and promising tool in many areas, including engineering‐related ones. Therefore, it has aroused growing interest in engineering education. The main objectives of this study are to examine engineering students' feedback and conceptual knowledge gain resulting from using an online AR app. The design and development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…In terms of concepts that are directly related to observations, the fact that the reviewer discovered also illustrates that the usage of this AR tool allows for a considerable transition from inaccurate responses to correct answers. This finding is consistent with a previous study [47] which found that if AR is implemented appropriately, it will be able to rectify student errors. Accordingly, the AR application employed in this study was demonstrated to have a successful instructional design as it achieved the goal for which it was created.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In terms of concepts that are directly related to observations, the fact that the reviewer discovered also illustrates that the usage of this AR tool allows for a considerable transition from inaccurate responses to correct answers. This finding is consistent with a previous study [47] which found that if AR is implemented appropriately, it will be able to rectify student errors. Accordingly, the AR application employed in this study was demonstrated to have a successful instructional design as it achieved the goal for which it was created.…”
Section: Discussionsupporting
confidence: 93%
“…The theory was chosen so that students are encouraged to construct ideas that are scientifically correct which would later bring about meaningful understanding in the students, including overcoming the misconceptions. Constructivist learning clearly differs from ordinary learning practices where the passive reception and transmission of information usually occurs from one individual to another [47]. In contrast, constructivism focuses on assisting students in moving from a preliminary understanding to a complete and real comprehension.…”
Section: Teaching and Learning Design Based-ar Applicationmentioning
confidence: 99%
“…When it comes to participant sample sizes, from Table 6 it is evident that in previous AR physics education research, student samples mostly included between 30 and 100 students. However, there were also 8 studies with more than 100 participants, and one of these studies included more than 400 participants [54]. In addition to students, some of the studies included also teachers who were asked about their thoughts on the AR approach to physics teaching.…”
Section: What Types Of Participants and How Many Of Them Were Include...mentioning
confidence: 99%
“…Target Population Approx. number of students References ARE "AR DC circuit puzzle" ME,CE, IEM,K12 900 [14], [15], [16], [17], [18], [19] "AR straightness evaluation" IEM 160 [19] "Groundwater flow on a small scale embankment dam" CE 170 [19] VE&Haptics " The purpose of the pre-test is to engage students in thinking about the physical phenomena they are about to observe and for possible explanations of the phenomena. Having observed and experimented, they can check whether their prediction is confirmed.…”
Section: Strategies Used To Evaluate the Oe Resourcesmentioning
confidence: 99%